2018
DOI: 10.1523/jneurosci.1734-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Spines in Early Postnatal Fragile X Mice Are Insensitive to Novel Sensory Experience

Abstract: Autism spectrum disorders are often associated with atypical sensory processing and sensory hypersensitivity, which can lead to maladaptive behaviors, such as tactile defensiveness. Such altered sensory perception in autism spectrum disorders could arise from disruptions in experience-dependent maturation of circuits during early brain development. Here, we tested the hypothesis that synaptic structures of primary somatosensory cortex (S1) neurons in Fragile X syndrome (FXS), which is a common inherited cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…We found that closing the pore with CoQ 10 on P9 acutely induced changes in morphology and density of dendritic spines in Fmr1 KOs. Because Fmr1 KO spines are pathologically unresponsive to novel sensory stimuli in the early postnatal period, our findings indicated modulation of spine dynamics following closure of the mPTP, similar to the long‐term potentiation‐induced spinogenesis seen shortly after theta‐burst stimulation in the normally developing rodent hippocampus 72,73 . Importantly, blocking the pathological leak on P9 normalized Fmr1 KO dendritic spine density several weeks later.…”
Section: Discussionsupporting
confidence: 57%
“…We found that closing the pore with CoQ 10 on P9 acutely induced changes in morphology and density of dendritic spines in Fmr1 KOs. Because Fmr1 KO spines are pathologically unresponsive to novel sensory stimuli in the early postnatal period, our findings indicated modulation of spine dynamics following closure of the mPTP, similar to the long‐term potentiation‐induced spinogenesis seen shortly after theta‐burst stimulation in the normally developing rodent hippocampus 72,73 . Importantly, blocking the pathological leak on P9 normalized Fmr1 KO dendritic spine density several weeks later.…”
Section: Discussionsupporting
confidence: 57%
“…These neurodevelopmental changes may be the result of atypical experience-dependent responses at the earliest stages of life. For example, FXS mice exposed to novel sensory input in the second postnatal week did not show the same significant increases in spine density as seen in wild-type mice [95]. However, mice that were exposed to enriched environments for longer periods of time had improved behavioral and morphological features, including more mature spines [96].…”
Section: Main Textmentioning
confidence: 99%
“…Indeed, it is increasingly recognized that some of the neural phenotypes reported in animal models of FXS and autism spectrum disorder (ASD) may reflect compensatory mechanisms or differential developmental experiences 44 , 45 . For example, it is well established that early differences in sensory experience, social interactions and maternal rearing, can alter numerous neural properties throughout life 47 53 . As a result of decreased social interactions, young FMRP-deficient animals could in effect inhabit an impoverished sensory environment.…”
Section: Introductionmentioning
confidence: 99%